(untitled) (JS (JURNAL SEKOLAH), 2021)
Abstract: Application Of Problem Based Learning Learning Models In Improving Mathematics Learning Outcomes Of Class VIII.4 Smp State 40 Palembang Students. The problem in this study is that most of the students of class VIII.4 SMP Negeri 40 Palembang do not understand the material in the Cartesian field. Starting from the description above, the problem in this study is formulated is how to improve mathematics learning outcomes after the implementation of the Problem Based Learning learning model for grade VIII.4 students of SMP Negeri 40 Palembang? . The expected objectives of this study were: to determine the increase in mathematics learning outcomes after the implementation of the Problem Based Learning learning model for class VIII.4 students of SMP Negeri 40 Palembang. The subjects in this study were 38 students of class VIII.4 SMP Negeri 40 Palembang. This research will be carried out in odd semesters in class VIII.4 of the 2018/2019 academic year from September to November 2018. This classroom action research has been said to be complete with evidence of an increase in Mathematics learning outcomes using the Problem Based Learning learning model for grade VIII.4 students. SMP Negeri 40 Palembang. Completeness of learning increased from pre-cycle, cycle I to cycle II, namely 47.37%, 71.05% and 92.11% respectively. In cycle II classical student learning completeness has been achieved and has increased very well. The conclusion is that the Problem Based Learning learning model can improve student learning outcomes. Keywords: Learning Outcomes, Mathematics, Problem Based Learning Learning Model Abstrak: Penerapan Model Pembelajaran Problem Based Learning Dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII.4 SMP Negeri 40 Palembang. Permasalahan dalam penelitian ini adalah sebagian besar siswa kelas VIII.4 SMP Negeri 40 Palembang kurang memahami tentang materi Bidang Kartesius. Bertitik tolak dari uraian di atas, maka dirumuskan masalah dalam penelitian ini adalah bagaimana peningkatan hasil belajar Matematika setelah diterapkannya Model pembelajaran Problem Based Learning siswa kelas VIII.4 SMP Negeri 40 Palembang?. Tujuan yang diharapkan dari penelitian ini adalah: untuk mengetahui peningkatan hasil belajar Matematika setelah diterapkannya Model pembelajaran Problem Based Learning siswa kelas VIII.4 SMP Negeri 40 Palembang. Subjek dalam penelitian ini adalah siswa kelas VIII.4 SMP Negeri 40 Palembang yang berjumlah 38 siswa. Penelitian ini akan dilaksanakan pada semester ganjil di kelas VIII.4 tahun ajaran 2018/2019 pada bulan September sampai dengan November tahun 2018. Penelitian tindakan kelas ini telah dikatakan tuntas dengan dibuktikannya peningkatan hasil belajar Matematika menggunakan Model pembelajaran Problem Based Learning siswa kelas VIII.4 SMP Negeri 40 Palembang. Ketuntasan belajar meningkat dari Pra siklus, siklus I ke siklus II yaitu masing-masing 47,37%, 71,05% dan 92,11% Pada siklus II ketuntasan belajar siswa secara klasikal telah tercapai dan mengalami peningkatan yang sangat baik. Kesimpulan bahwa Model pembelajaran Problem Based Learning dapat meningkatkan hasil belajar siswa. Kata Kunci: Hasil Belajar,Matematika, Model pembelajaran Problem Based Learning